Carotid-Cavernous Fistulas: The Utility of Ocular Echography in Their Differentiation [Response to Letter] - Supasai P; Kanjana K; Yospaiboon Y (Clinical Ophthalmology, 2023)
Pawasoot Supasai, Kanwasee Kanjana, Yosanan Yospaiboon KKU Eye Center, Department of Ophthalmology, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Yosanan Yospaiboon, KKU Eye Center, Department of Ophthalmology, Faculty of Medicine, Khon Kaen University, 123 Mitraparb Highway, Khon Kaen, 40002, Thailand, Tel +66-4336-3010, Fax +66-4334-8383, Email yyosanan@gmail.com